Arsitektur Drama Rainbow: Poetri Kentjana Boelan - Irianto, Ikhsan Satria; Rifandi, Ilham; Handayani, Lusi; Gustyawan, Tofan (Jurusan Sejarah, Seni, dan Arkeologi, FKIP Universitas Jambi, 2023)
The architectural analysis of Soekarno's drama Rainbow: Poetri Kjencana Boelan aims to trace the design of Soekarno's dramatic work, as a preliminary study of Soekarno's dramatic vision. The material object in this research is the drama Rainbow: Poetri Kjencana Boelan while the analytical tool used is the theory of drama architecture from Ledwin, Joe and Stockadale. The research method used is a qualitative method with a text analysis approach. The result of this research is that the drama Rainbow: Poetri Kjencana Boelan has the theme of revenge, uses multi-plots (linear and episodic), designs characterizations in black and white characters and has a tragedy genre and a romantic style. The writing of the drama Rainbow: Poetri Kjencana Boelan was influenced by the spirit of the times